Explicitly connecting ideas: How well is it done? - Hurst, Chris; Huntley, R. (MERGA, 2017)
Multiplicative thinking is a critical stage of mathematical understanding upon which many mathematical ideas are built. The myriad aspects of multiplicative thinking and the connections between them need to be explicitly developed. One such connection is the relationship between place value partitioning and the distributive property of multiplication. In this paper we explore the extent to which students understand partitioning and relate it to the distributive property and whether they understand how the property is used in the standard multiplication algorithm.